INDONESIA'S MANPOWER BEHAVIOR IN MANAGING FUNDS FOR SUSTAINABILITY - Dhiya Hanis Durrani; Firman Ardiansyah; Agus Sukoco; Santirianingrum S; Wahyu Mulyo Utomo (Journal of International Conference Proceedings (JICP), 2018)
The purpose The purpose of research to find the effect of short-term debt owned by the company on increasing or decreasing the liquidity ratio and in specializing in research on consumption companies in Indonesia. Methodology, analyzing the liquidity ratio in this case is done by working capital method to total assets ratio. The population of this study amounted to five companies. Procedure criteria of selecting the sample using purposive sampling with the financial statements of 2013. Result, short-term debt has an average value of 45 billion and the liquidity ratio has an average value of 35.1 times, the relationship between shortterm debt and liquidity ratio is positive with the smallest 0.38 and 0.56. Current liabilities have a positive effect on liquidity ratios in the five companies studied The findings ,the value of R2basically illustrates how much the relationship between dependent and independent variables, which concluded shortterm debt can explain the liquidity ratio of 3,9%. A small R2value implies that the variable X influences the variable Y Keywords: short-term debt, liquidity ratio